Lying flat to play on smartphone excessively: the role of self-esteem - Zhu, Shuhua; Wang, Lishen; Gan, Yulu (Frontiers in Psychology, 2025)
IntroductionWith the rapid development of their countries, Chinese young people today face intense stress. Some cope by striving for high-quality resources (involution), while others adopt a passive approach, lowering their desires (lying flat). This study explores the relationship between lying flat and problematic smartphone use (PSU), focusing on the role of self-esteem.MethodsWe conducted three studies (N = 886) using both cross-sectional (Study 1) and experimental (Study 2 and Study 3) designs to examine the correlational and causal links between lying flat, self-esteem, and PSU.ResultsThe studies demonstrated a significant relationship between lying flat and PSU, with self-esteem serving as a mediator. Additionally, Study 3 showed a causal effect of self-esteem on smartphone use desire.DiscussionThese findings provide insight into why and how lying flat affects self-esteem and smartphone use behaviors and desires, highlighting the psychological mechanisms behind the trends observed in Chinese youth.